Analisis sikap dan minat konsumen dalam mengambil polls asuransi jiwa pada industri asuransi di Kotamadya Malang: study kasus pada masyarakat penghuni perumahan KPR-BTN) = The Analysis of The Consummer's Attitude and ... - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1995)
The development of life insurance especially in Indonesia hasn't been properly considered, recently. The life insurance policy holders in Indonesia have only reached 1,68%, whereas Japan